Síntese, modelagem molecular e avaliação da atividade anticolinesterásica de N,N-dimetilcarbamatos de cicloexila 3-arilaminossubstituídos - Yamazaki, Diego Alberto dos Santos (2015)
The carbamate group has great pharmacological importance as a cholinesterase inhibitor and in the treatment of Alzheimer's disease. The present study describes the synthesis, conformational analysis, assessment of the anticholinesterase activity and the mode of inhibition of two new series of cis and trans-N,N-dimethylcarbamate of 3-arylaminesubstituted-cyclohexyl. Compounds were synthesized, purified and characterized by NMR spectroscopy analysis of 1H, 13C and HSQC. The conformational equilibrium of the carbamates has been experimentally determined and compared to data obtained from electronic structure calculations. The Dynamic NMR experiments showed that the conformational equilibrium of the compounds is not influenced by the variation of solvents. For the trans-N,N-dimethylcarbamate of 3-fenylaminecyclohexyl (4a), the conformer AE presented a contribution of ca. 90% on the conformational equilibrium. For the cis-N,N-dimethylcarbamate of 3-fenylaminecyclohexyl (5a) the diequatorial conformer (EE) was dominant in the equilibrium, and in most polar solvents the diaxial conformer (AA) was not observed. The results obtained from calculations using the theory levels M06-2X/6-311++G(d,p) and M06-2X/6-311++G(2df,2p) for the trans isomer were in agreement with the data experimentally obtained. However, for the cis isomer, was only possible to reproduce the trend experimentally observed in M06-2X/6-311++G(2df,2p). The tested carbamates exhibited a dose-dependent inhibitory action on cholinesterase and all compounds were selective for BuChE enzyme with IC50 values between 0.11 and 0.18 mmol / L. The hydrochloride of cis and trans N,N-dimethylcarbamate 3-(4-methoxyphenylamino) cyclohexyl (6c and 7c) were the most active for BuChE, showing that the presence of methoxyl group enhanced the anticholinesterase activity. In general, these compounds showed an inhibitory potential greater than its 1,2-disubstituted analogs, indicating that changing the arylamine group to position 3 of the cyclohexyl ring the activity against the BuChE enzyme were enhanced. The enzyme kinetics study indicates a noncompetitive inhibition against AChE and mixed type inhibition for BuChE. This difference in the mode of inhibition can explain the higher activity of BuChE front the carbamates studied because the mixed type inhibitor binds both the free enzyme and enzyme-substrate complex. The study of molecular docking and non-covalent interactions (NCI) were in agreement with the experimental results. Molecular docking showed that the compound 6c interacts with the peripheral anionic site and the catalytic active site of BuChE, while in AChE interactions only occur in the catalytic active site. The NCI analysis indicated that the compound 6c showed better stabilization in the active site of BuChE than in the active site of AChE, explaining the selectivity for BuChE